UN decade of education for sustainable development:perceptions of portuguese’s higher education institutions - Aleixo, Ana Marta (2016)
This poster shows partial results of a cross-sectional research project investigating the perceptions of stakeholders of four Portuguese Higher Education Institutions about the importance of integration Sustainable Development (SD) in Higher Education Institutions (HEIs).